Integrating micro-learning and station rotation blended learning model: enhancing Japanese communication skills of Chinese undergraduates - Hu, Xinyue; Sriwisathiyakun, Kanyarat; Sitthiworachart, Jirarat (My University, 2025)
In the rapidly evolving language education landscape, integrating innovative pedagogical approaches is essential to meet the diverse needs of learners. This study explores the efficacy of a Micro-Learning Media with Station Rotation Blended Learning Model (MLM-SRM) in enhancing the Japanese communication skills—specifically speaking, listening, and reading—of second-year students at Sichuan University. The research employed a pre-test-post-test randomized controlled experimental design, involving 80 students who were randomly assigned to either the MLM-SRM group or a traditional teaching group. Data were collected using well-established rubrics for speaking, listening, and reading skills, and analyzed through mean, standard deviation, Cohen’s d, and one-way MANOVA. The results revealed that students in the MLM-SRM group significantly outperformed those in the traditional group in overall language proficiency, with the most substantial gains observed in reading skills, followed by speaking and listening. A deeper analysis highlighted significant improvements in interactive communication for speaking, interactive and response skills for listening, and text structure for reading among the MLM-SRM participants. Furthermore, a thematic analysis of students’ open-ended survey responses underscored a positive reception towards the MLM-SRM, indicating its potential as an effective tool for language instruction. These findings underscore the importance of the MLM-SRM approach, which immerses students in an engaging and diverse learning environment and holds significant implications for theory and practice. This approach can potentially transform how languages are taught and learned globally.
Keywords: Communication skills; Listening skills; Micro-learning; Reading skills; Speaking skills; Station rotation